Anemia aplástica e exposição a agrotóxicos : um estudo no estado de Mato Grosso - Bezerra, Rita de Cássia Gomes (2021)
Aplastic anemia is a rare hematologic disease that can have hereditary origin or acquired origin. Many studies associate acquired aplastic anemia with various causes, including chemical agents, especially pesticides. General objective: To investigate the relationship between aplastic anemia and exposure to pesticides, from 2000 to 2019, in the state of Mato Grosso. Method: This is a study with exploratory descriptive epidemiological design. Data collection, of an exploratory nature, consisted of three stages: In the first, a descriptive analysis of information contained in the Medical Records of patients diagnosed with aplastic anemia and hypoplasia,treated at the Coordinating Hemocenter from 2000 to 2019, was performed. In the second stage, the spatial distribution of aplastic anemia cases by municipality in the state of Mato Grosso and of planted areas by type of agricultural crop was performed to estimate the amount of pesticides consumed by municipality in the year 2019, according to PIGNATI (2017) methodology. The third stage, of an exploratory nature, consisted of a telephone interview.Twenty patients diagnosed with aplastic anemia were selected for a telephone interview.For the analysis of the interviews, Content Analysis was used in the thematic modality. Four (04) categories were established: Socioeconomic factors and health vulnerability; Use of pesticides in the environment and Health Surveillance; Risk perception: relationship between aplastic anemia and pesticides in the interlocutors' conception; Invisibility of domestic exposure risks associated with the use of pesticides. Results: 104 medical records diagnosed with aplastic anemia/bone marrow hypoplasia were analyzed. It was observed that most cases had a diagnosis of unspecified aplastic anemia (D61.9) - 45.2%; there was no difference between genders: 50% male, 50% female; brown race/color prevailed (57.7%); incomplete primary education accounted for 26.9% of cases; single marital status prevailed (48.1%); most had urban origin (77.9%); regarding the distribution of occupations, 17.3% of the cases had "Ignored" occupation, agricultural, forestry and fishing workers represented 12.5% of cases and students 12.5% of cases, followed by homeworkers - 11, 5%. At the end of the study period, the majority (70.2% of cases) were still alive and 13.5% died from aplastic anemia. The majority (87.5% of cases) came from four regions, according to the Mato Grosso Institute of Agricultural Economics (IMEA): Center-South, West, Middle-North and Southeast. In 2019, the planted area in Mato Grosso was 16.5 million hectares, with 245 million liters of pesticides being used in these crops. Conclusions: In the Coordinating Hemocenter in the state of Mato Grosso, the diagnosis of aplastic anemia of the unspecified type was highlighted, in younger, brown, single, low-educated individuals, with occupation focused on agriculture and livestock and residents of urban areas. It is also noteworthy that it was not possible to perform a deeper analysis of the relationship between exposure to pesticides and the occurrence of AA due to the incompleteness of data records in the medical records of the reference service and the absence of systematic records of data on occupational and environmental exposure to chemical agents, known to be associated with the etiology of AA. There was no record of income. It is considered that agricultural production and consumption of pesticides are increasing in Mato Grosso, contributing to the increased risk of exposure of this population. Of the 20 interviews conducted, according to the perception of the participants, there was child exposure by parental occupation. In general, environmental, household and occupational exposures have been reported, especially of rural workers. The results of this study may contribute with important information for the implementation of the registries in the Coordinating Hemocentre of Mato Grosso, and with the description of the epidemiological profile of AA followed up at the reference service. It is also noteworthy that the data point to the importance of monitoring multiple exposures to pesticides in the state, including exposures to which patients with hematological diseases are subject.